Peran Pendidikan dan Lingkungan dalam Mempersiapkan Kemandirian Karir Remaja - Susidah Ernawati; Hardiyawansyah Hardiyawansyah; Mgs Hasrul Haris; Sani Safitri; Syarifuddin Syarifuddin (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Adolescent career independence is a crucial aspect in facing the increasingly competitive world of work. This article discusses the role of education and environment in shaping adolescent career independence. Education, both formal and non-formal, provides the foundation of skills and knowledge needed to enter the world of work. On the other hand, the environment, including family, peers, and social communities, plays a role in shaping adolescents' mindsets, values, and motivations in planning their future. This study uses a qualitative approach with a literature study to explore the factors that influence adolescent career independence. The results show that quality education, effective career guidance, and positive environmental support contribute greatly to increasing adolescent readiness to make career decisions independently. In conclusion, collaboration between education, family, and society is key to building a young generation that is independent and ready to face the challenges of the world of work.